Factors Affecting Hospital Length of Stay in Patient with Diabetic Foot Ulcer - Patrianef Darwis; Bakti H Simanjuntak; Grace Wangge; Deddy Pratama; Ahmad Bakri; Rizky Telaumbanua (Ikatan Ahli Bedah Indonesia, 2019)
Background. Foot ulcer is one of the most common complications in diabetes mellitus patients. This condition prolongs hospital length of stay (LOS) and increases hospitalization cost. This study aims to assess factors that affect the LOS in patients with the mentioned condition. Methods. This is a retrospective cohort study of diabetes mellitus patients with foot ulcer who were hospitalized in Cipto Mangunkusumo General Hospital from January 2015 to April 2016. There were 120 patients recruited and then divided into two groups according to their hospitalization duration, which was short and long. Univariate analysis was conducted in predicted factors including gender, ankle-brachial index, ulcer size, ulcer depth, leukocyte count, treatment, cardiovascular comorbidity, blood pressure, smoking history, septicemia, ketoacidosis, hypoalbuminemia, and upper respiratory tract infection. Chi-Square tests were performed to analyze the association of those factors with LOS. The odds ratio of each variable was evaluated using logistic regression analysis. Result. In this study, the mean of LOS was 26 days (2 – 87 days). Factors that significantly correlated with LOS were ankle-brachial index (p 0.041, OR 2.275, CI 95 % 1.025 – 5.041), ulcer size (p 0.044, OR 3.038, CI 95 % 1.032 – 9.942), smoking history (p 0.022, OR 2.434, CI 95 % 1.125 – 5.265), sepsis (p < 0.001, OR 4.240, CI 95 % 1.908 – 9.423), and ketoacidosis (p < 0.001, OR 8.611, CI 95 % 3.396 – 21.835) In multivariate analysis, the most significant factor was ketoacidosis (p < 0.001, OR 8.360, CI 95 % 3.209 – 21.780). Conclusion. Ketoacidosis is the most significant factor that prolonged hospital stays in a patient with diabetic foot ulcer. Keywords: Diabetic foot ulcer, Length of stay